M17 Investigating indoleamine 2, 3 dioxygenase (IDO) activity in bronchiectasis and COPD. (12th November 2019) - Potter, R; Huan, L; De Soyza, A; Mellor, A
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) and bronchiectasis are both progressive and largely irreversible inflammatory lung diseases. Bronchiectasis is a chronic airway inflammation syndrome associated with excessive mucus production. Indoleamine 2, 3-dioxygenase (IDO) activity as evidenced by kynurenine/tryptophan ratio is a marker interest as prior evidence suggests a potential role in COPD, pneumonia and TB. Available data suggests that IDO might be upregulated during COPD exacerbations but data are conflicting. IDO may be important in both antibacterial responses and adaptive immunity. Methods: We interrogated a biobank of samples with clinical metadata. Sputum and serum samples were analysed using HPLC to detect kynurenine (KYN) and tryptophan TRY) levels and IDO activity inferred by K/T ratios. Results: The COPD and HV patient cohorts were significantly smaller than in bronchiectasis (58, 25 and 150 samples respectively), and the number of matched sputum samples was 65. In bronchiectasis and healthy volunteer patients increasing age positively correlated with IDO activity ((K/T ratio; p=0.0204, p=0.0062) in blood samples. Additionally IDO activity in sputum was higher in more severe bronchiectasis (p=0.0221), asthma (p=0.0443) and immunodeficiency status (p=0.0449). A significant difference was seen in the IDO activity of bronchiectasis sputum when compared to blood samples of bronchiectasis. A significant positive correlation was seen between KYN levels in plasma and age (p=0.01), whereas a negative correlation was seen between this and immunodeficiency (p=0.046). The K/T ratio of the plasma showed a positive correlation with age as well (p=0.012). In the sputum a positive correlation was seen between KYN and bronchiectasis severity index (p=0.025), pseudomonas history (p=0.045), and with comorbid COPD/BCOS (p=0.022). In contrast IDO in COPD samples had no correlation with no clinical parameters. Conclusion: This suggests that IDO activity in sputum varies by severity and aetiology in Bronchiectasis. It may prove useful in defining distinct subgroups. Further study to understand the differences in IDO activity during stable state and after treatment for exacerbations will help further define the role of this pathway in Bronchiectasis and COPD.